Day 2 Tue, August 03, 2021 2021
DOI: 10.2118/207129-ms
|View full text |Cite
|
Sign up to set email alerts
|

Artificial Intelligence Model for Predicting Formation Damage in Oil and Gas Wells

Abstract: An artificial neural network (ANN) was developed to predict skin, a formation damage parameter in oil and gas drilling, well completion and production operations. Four performance metrics: goodness of fit (R2), mean square error (MSE), root mean square error (RMSE), average absolute percentage relative error (AAPRE), was used to check the performance of the developed model. The results obtained indicate that the model had an overall MSE of 355.343, RMSE of 18.850, AAPRE of 4.090 and an R2 of 0.9978. All the pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 19 publications
1
2
0
Order By: Relevance
“…In Table 7, the R 2 and R values show that the developed neural-based models predicted integral values were close to the actual values provided by Poettmann [14]. This statement is because the R 2 and R values for the various neural-based models were close to 1, which statistically means a good fit between the predicted and actual values [29,31]. Again, the good fits of the developed neural-based models are further observed in Fig.…”
Section: Comparison Of the Developed Neural-based Models Predictions ...supporting
confidence: 64%
See 1 more Smart Citation
“…In Table 7, the R 2 and R values show that the developed neural-based models predicted integral values were close to the actual values provided by Poettmann [14]. This statement is because the R 2 and R values for the various neural-based models were close to 1, which statistically means a good fit between the predicted and actual values [29,31]. Again, the good fits of the developed neural-based models are further observed in Fig.…”
Section: Comparison Of the Developed Neural-based Models Predictions ...supporting
confidence: 64%
“…The overall R-values for the 2-5-1 topology indicated that the developed network could predict Poettmann's integral values with 99.870% and 99.92% certainty with the maximum-minimum and clip normalization methods. According to Sircar et al [30] and Effiong et al [31], the mathematical representation of the neural network computations parameters (i.e., inputs, weights, biases, and output) in vector form and transfer or activation functions (i.e., tansig and purelin) are related, as expressed in Equation 5;…”
Section: Performance Of the Developed Neural Networkmentioning
confidence: 99%
“…The limitation alluded to most neural network models in the literature is the availability of the essential details of the models for their reproducibility. One such detail is the weights and biases of the neural network [22]. This study's weights and biases of the BS&W network are depicted in Table 4.…”
Section: Basic Sediment and Water (Bsandw) Neural Network Performancementioning
confidence: 99%